NEW HORIZONS OF ENVIRONMENTAL EDUCATION: FROM THE NOOSPHERIC WORLDVIEW TO THE NOOSPHERIC ETHICS - Sergey A. Ivanov (Russian State Vocational Pedagogical University, 2015)
The aim of the study is to identify promising areas of the development of environmental education at secondary school and a substantiation of the urgent decision necessity of a problem of formation noospheric vision of the world by the students. Methods. The methods involve logical-methodological and historical and methodological analysis of some concepts; theoretical analysis of philosophical, psychological, pedagogical and sociological literature; analysis of existing programs, textbooks on Natural Sciences of the secondary school; modeling of contents science education. Results. The necessity of the complex approach to development of ecocentric ecological consciousness and formation of noospheric worldviews among school students is proved on the basis of the philosophical and psychologicalpedagogical analysis of concept "view of the world" and estimations of prospects of development of a human civilisation. The structure of the view of the world is presented; the principles including moral basis and ethical standards which are required to be mastered by pupils of educational institutions are defined. Scientific novelty. The definition of noospheric worldviews is given; its structure and the basic channels of formation are shown: cognitive (translation of knowledge about the world and the person), perceptive (involving in educational process of emotions and feelings), and practical (inclusion of the person in socially-significant, nature-aligned, creative activity). Practical significance. The research findings can be useful while modeling the environmental education in educational institutions; practical work of teachers, teachers of an additional education; development of training programs and manuals, contributing to the spread of knowledge on ecology, integrity of the Universe, noospheric ethics, and importance to civilisation preservation of naturealigned attitude of the person to the world around.